Nonspecific Genitourinary Pain Improves after Prostatectomy Using Holmium Laser Enucleation of Prostate in Patients with Benign Prostatic Hyperplasia: A Prospective Study - Kim, Sung Han (Public Library of Science, 2014)
OBJECTIVE: To investigate changes in nonspecific genitourinary discomfort or pain (GUDP) before and after holmium laser enucleation of prostate (HoLEP). GUDP associated with lower urinary tract symptoms (LUTS) is a common complaint among benign prostatic hyperplasia (BPH) patients, but very little is known about this clinical entity. METHODS: From February 2010 to August 2011, 100 HoLEP patients with complete clinical data at a single institution were enrolled in the study to analyze the degree of GUDP with a visual analog scale (VAS) from 0 to 10 points at baseline and at 3 and 6 months postoperatively, and to investigate any relationships between GUDP and urodynamics, uroflowmetry, and scores from the International Prostate Symptom Score (IPSS) questionnaire. RESULTS: Fifty-six patients had LUTS only, while the remaining 44 had both LUTS and GUDP. Pain was located in the suprapubic (42.0%), perineal/penile (33.0%), back (17.0%), and perianal (8.0%) regions. During the post-operative period, at six months, the VAS, IPSS, peak flow rate and post-void residual volume had improved significantly in 44 GUDP patients (p<0.010). GUDP had completely resolved in 40 (90.9%) patients and had decreased in four (9.1%) patients, while seven (12.5%) patients developed GUDP with voiding in the urethral and perineal areas by the third month postoperatively. When compared to patients with complete resolution, those with persistent GUDP were found to have a significantly higher preoperative presence of bladder outlet obstruction (BOO) as an independent risk factor (OR 6.173, 95% CI 1.132–1.323). CONCLUSION: Both GUDP and LUTS improved significantly after HoLEP. Patients with significant preoperative BOO tended to have persistent GUDP after surgery.